Dendrimer functionalized folate-targeted gold nanoparticles for luciferase gene silencing in vitro: A proof of principle study - Mbatha Londiwe Simphiwe; Maiyo Fiona Chepkoech; Singh Moganavelli (Acta Pharmaceutica)
Use of exogenous small interfering RNA (siRNA) has shown potential in gene silencing. The need for target-specific siRNA delivery vehicles is crucial to successful gene silencing. This study is aimed at developing and evaluating the safety and efficiency of siRNA delivery using unmodified and folic acid (FA) modified poly(amidoamine) generation 5 (PAMAM G5D) functionalized gold nanoparticles (Au:G5D/Au:G5D:FA) in vitro. All formulations were physico--chemically characterized and nanocomplexes were evaluated using the band shift, dye displacement, nuclease protection, MTT cell viability, and luciferase reporter gene assays. Nanocomplexes bound and protected siRNA against degrading RNases, and were well tolerated by the cells. The Au:G5D:FA nanocomplexes elicited excellent gene silencing in folate receptor expressing HeLa-Tat-Luc cells, decreasing significantly in the presence of excess FA ligand, indicating nanocomplex uptake by the mechanism of receptor mediation. These results highlight the synergistic role played by Au and the dendrimer in enhancement of transgene silencing.